2015
DOI: 10.1021/ja511371a
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene-Catalyzed Radical Reactions for Highly Enantioselective β-Hydroxylation of Enals

Abstract: An N-heterocyclic carbene-catalyzed β-hydroxylation of enals is developed. The reaction goes through a pathway involving multiple radical intermediates, as supported by experimental observations. This oxidative single-electron-transfer reaction allows for highly enantioselective access to β-hydroxyl esters that are widely found in natural products and bioactive molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
77
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(88 citation statements)
references
References 45 publications
3
77
0
6
Order By: Relevance
“…Evidence points to one electron oxidation of the homoenolate equivalent 6 by an electron deficient nitroarene oxidant. 7,8 During our investigations, we observed the formation of cyclopentanone products 9 when the reaction is conducted in a non-nucleophilic solvent. For example, the reaction of 4-methoxycinnamaldehyde 1a with 4-nitropyridine N-oxide 2 in dichloromethane at room temperature in the presence of NHC 3a forms cyclopentanone 4a in 49 % yield as a single diastereomer.…”
mentioning
confidence: 81%
“…Evidence points to one electron oxidation of the homoenolate equivalent 6 by an electron deficient nitroarene oxidant. 7,8 During our investigations, we observed the formation of cyclopentanone products 9 when the reaction is conducted in a non-nucleophilic solvent. For example, the reaction of 4-methoxycinnamaldehyde 1a with 4-nitropyridine N-oxide 2 in dichloromethane at room temperature in the presence of NHC 3a forms cyclopentanone 4a in 49 % yield as a single diastereomer.…”
mentioning
confidence: 81%
“…In 2008, Studer et al 7 reported the NHC-catalyzed conversion of enals to esters using TEMPO as a single-electron oxidant (Scheme 1, reaction c). During our investigation of this work, the single electron oxidation of the homoenolate was pioneered by Rovis et al 8 and Chi et al 9 (Scheme 1, reaction d). The oxidative homo and cross-coupling of the two homoenolates was established by Rovis et al (Scheme 1, reaction e).…”
Section: Introductionmentioning
confidence: 99%
“…Chiral enamines 4 can undergo single electron transfer to generate a chiral radical species that then combines with a radical electrophile, as described by the Sibi [14] and MacMillan [15] laboratories. [16,17] …”
mentioning
confidence: 99%